Genetic factors affecting risk of pre-eclampsia and its complications – a hugenet field overview and meta-analysis. (18th April 2012) - Fong, F; Sahemey, M; Walton, R; Thangaratinam, S
Abstract : Background: Pre-eclampsia is a leading cause of maternal and perinatal morbidity and mortality. Although much research has centred on this clinical phenomenon, the underlying pathogenetic mechanisms remain unclear. Immune maladaptation, placental ischaemia and increased oxidative stress represent the main aetiologically important factors, all of which may have genetic implications. Twin and family studies support the familial contribution to pre-eclampsia and suggest that common alleles act as 'susceptibility genes' although the pattern of inheritance is unclear. Objective: To evaluate the maternal and paternal genetic effects on pre-eclampsia. Methods: We performed a HuGeNet (Human Genome Network) systematic field review of all relevant studies in major databases. Studies (including twin and family studies) that evaluated the genetic effects on pre-eclampsia were included. The inclusion criteria consisted of evaluation of genes, gene variations in pregnant women or women with a history of pre-eclampsia with outcomes of pre-eclampsia, maternal and fetal complications. We included maternal and paternal contributions and definition of phenotype. The Hardy-Weinberg Equilibrium was calculated for each polymorphism to assess risk of bias. Results: We identified 294 studies by literature search. Each study was ranked independently according to the quality. The common genes with an association with development of pre-eclampsia were eNOS, VEGF, HLA-G, MTHFR, leptin receptor, Factor V Leiden and TNF alpha. We will provide individual numerical results of the strength of association if selected for presentation.